Convection analysis of the radiative nanofluid flow through porous media over a stretching surface with inclined magnetic field - Hussain, Muzamil (International communications in heat and mass transfer)
Nanofluids flow through porous media constitutes an emerging perspective in many thermodynamic processes and thermal processing optimization. The primary goal of contemporary research from the standpoint of such thermal applications is to examine the nanofluid flow across a vertically placed stretching surface embedded in a porous media. The mathematical formulation of the considered flow is modeled with the consequences of inclined magnetic field and thermal radiations. The Darcy-Forchheimer-Brinkman model addresses the fluid transport within the porous medium. Carbon nanotubes (CNTs) and alumina ceramics are considered nanoparticles and porous media, respectively, and water is regarded as a base fluid in this study. Appropriate transformations have been developed to reduce the governing equations into the dimensionless system. The highly nonlinear transformed system is addressed by using a local non-similarity approach via the bvp4c built-in MATLAB function. The physical implications of the emerging dimensionless parameters on the velocity and thermal profiles of considered nanofluids are studied and discussed in detail. It is perceived that the thermal profile of nanofluid is enhanced with increasing estimations of nanoparticles concentrations and radiation parameters. Furthermore, an increment in Hartmann's number and magnetic field inclination angle diminishes fluid velocity. Furthermore, increasing the Darcy number reduces the temperature distributions of the nanofluids under consideration. Comparing the current study with published articles is also performed to corroborate the reported results. In this regard, an excellent agreement has been achieved. This work is expected to provide important information for the future implementation of innovative heat transfer devices, as well as a valuable reference for researchers studying nanofluids flows under varied assumptions.